1991
DOI: 10.1007/bf02662156
|View full text |Cite
|
Sign up to set email alerts
|

Determination of molecular species of oil triacylglycerols by reversed‐phase and chiral‐phase high‐performance liquid chromatography

Abstract: A method is described for the determination of molecular species of oil triacylglycerols. The method is based on the analytical separation of the enantiomeric sn-l,2-and sn-2,3-diacylglycerols, derived from triacylglycerols, by high-performance liquid-chromatography (HPLC) on a chiral column containing N-(R)-l-(a-naphthyl)ethylaminocarbonyl-(S)-valine as stationary phase. Model triacylglycerol molecules comprising three known fatty acids were isolated from peanut oil and cottonseed oil by a combination of arge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
3
7
1
Order By: Relevance
“…Oleic acid was also the main fatty acid in the sn-3 position followed by palmitic, stearic, linoleic, linolenic, and palmitoleic acid. This differed from others who reported that the fatty acids located at the sn-3 position was highly influenced by their respective concentration in the total fatty acids at the other positions [8,15,16]. Palmitic acid and stearic acid were distributed primarily in the sn-1 and sn-3 positions, while oleic acid and linoleic acid were found in greater amounts at the sn-2 position.…”
Section: Sircontrasting
confidence: 83%
See 1 more Smart Citation
“…Oleic acid was also the main fatty acid in the sn-3 position followed by palmitic, stearic, linoleic, linolenic, and palmitoleic acid. This differed from others who reported that the fatty acids located at the sn-3 position was highly influenced by their respective concentration in the total fatty acids at the other positions [8,15,16]. Palmitic acid and stearic acid were distributed primarily in the sn-1 and sn-3 positions, while oleic acid and linoleic acid were found in greater amounts at the sn-2 position.…”
Section: Sircontrasting
confidence: 83%
“…In most vegetable oils, unsaturated fatty acids occupy the sn-2 position and saturated fatty acids are located in the sn-1 and sn-3 positions. The preponderance of linoleic acid at the sn-2 position is well known in vegetable oils [5,8,16]. The distribution of fatty acids between sn-1 and sn-3 position was nearly symmetrical for palmitic acid, stearic acid, and oleic acid, which is in agreement with Brockerhoff and Yurkowski [8].…”
Section: Sirsupporting
confidence: 73%
“…In most vegetable oils, unsaturated fatty acids occupy the sn-2 position, and saturated fatty acids are located more in the sn-1 and sn-3 positions. The preponderance of more unsaturated fatty acids at the sn-2 position is well known in vegetable oils [9,13,14]. The distribution of saturated fatty acids (palmitic and stearic acids) was more pronounced at sn-1 and 3 rather than at sn-2, which is in agreement with data reported earlier.…”
Section: Sirsupporting
confidence: 89%
“…At sn ‐2 and 3 positions, however, the linoleic acid was present more than the stearic acid. It is well known that the unsaturated fatty acids occupy more at the sn ‐2 position in most vegetable oils, whereas the saturated fatty acids are located more at the sn ‐1 and sn ‐3 positions (Brockerhoff and Yurkowski 1966; Sempore and Bezard 1991). The preponderance of the unsaturated fatty acids, such as the oleic and linoleic acids (totally 96.4%) at the sn ‐2 position is clearly elucidated in the camellia oil.…”
Section: Resultsmentioning
confidence: 99%